2023
DOI: 10.1590/1984-3143-ar2023-0017
|View full text |Cite
|
Sign up to set email alerts
|

Full confluency, serum starvation, and roscovitine for inducing arrest in the G0/G1 phase of the cell cycle in puma skin-derived fibroblast lines

Abstract: The puma population is constantly decreasing, and cloning by somatic cell nuclear transfer can be used to conserve the species. One of the factors determining the success of the development of cloned embryos is the cell cycle stage of the donor cells. We evaluated the effects of full confluency (~100%), serum starvation (0.5% serum), and roscovitine (15 µM) treatments on the cell cycle synchronization in G 0 /G 1 of puma skin-derived fibroblasts by flow cytometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
0
1
Order By: Relevance
“…This could be because blastocysts were cultured without any protein supplementation 12 h prior to media collection, and their cells could have been in a quiescent stage, affecting their protein expression and secretion. Several studies have reported how serum or protein deprivation induces G0/G1 arrest in in vitro-cultured somatic cells of felids [135][136][137]. However, we observed that different types of specific proteins were released by the ZF and ZI blastocysts.…”
Section: Discussioncontrasting
confidence: 51%
“…This could be because blastocysts were cultured without any protein supplementation 12 h prior to media collection, and their cells could have been in a quiescent stage, affecting their protein expression and secretion. Several studies have reported how serum or protein deprivation induces G0/G1 arrest in in vitro-cultured somatic cells of felids [135][136][137]. However, we observed that different types of specific proteins were released by the ZF and ZI blastocysts.…”
Section: Discussioncontrasting
confidence: 51%